Shaping of Electron Beams Using Sculpted Thin Films - Roitman, Dolev; Shiloh, Roy; Lu, Peng Han; Dunin-Borkowski, Rafal E.; Arie, Ady (ACS Photonics, 2021)
Electron beam shaping by sculpted thin films relies on electron-matter interactions and the wave nature of electrons. It can be used to study physical phenomena of special electron beams and to develop technological applications in electron microscopy that offer new and improved measurement techniques and increased resolution in different imaging modes. In this Perspective, we review recent applications of sculpted thin films for electron orbital angular momentum sorting, improvements in phase contrast transmission electron microscopy, and aberration correction. For the latter, we also present new results of our work toward correction of the spherical aberration of Lorentz scanning transmission electron microscopes and suggest a method to correct chromatic aberration using thin films. This review provides practical insight for researchers in the field and motivates future progress in electron microscopy.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Aberration correction; Beam shaping; Electron microscope; Orbital angular momentum; Phase masks